Advanced screen-printed electrode functionalized ZnO/CNTs for the electrochemical analysis of opioid drug pethidine co administered with paracetamol: application in dosage form and human plasma sample - Shimaa A. Atty; Ahmed M. Abdelzaher; Sona Barghash; Mona A. Abdel Rahman (BMC Chemistry)
Abstract Synthetic opioids such as pethidine (PTD) have a high potential for addiction but are widely used in clinical settings to manage pain before and after surgical procedures. Combinations of pethidine (PTD) with paracetamol (PCM) are frequently prescribed for the treatment of severe and chronic pain. In this study, an eco-friendly voltammetric sensor based on a screen-printed electrode (SPE) modified with zinc oxide nanoparticles functionalized with carbon nanotubes (ZnO/CNTs) was developed and employed. For the first time, the proposed sensor was successfully applied for the determination of pethidine in pharmaceutical formulations, demonstrating excellent recovery. Furthermore, it enabled the simultaneous detection of pethidine and paracetamol in biological samples, with low detection limits of 980 pmol L⁻1 and 977 pmol L⁻1 for PTD and PCM, respectively. The sensor offers a promising tool for point of care diagnostics and routine analysis due to its sensitivity, simplicity, and cost-effectiveness.